Compressive strength and interfacial transition zone of sugar cane bagasse ash concrete: A comparison to the established pozzolans - Hussein, A.A.E. (American Institute of Physics Inc., 2015)
Agricultural and industrial by-products are commonly used in concrete production as cement replacement materials (CRMs) or as admixtures to enhance both fresh and hardened properties of concrete as well as to save the environment from the negative effects caused by their disposal. Sugar Cane Bagasse Ash (SCBA) is one of the promising CRMs, it is used as a partial replacement of cement for producing concrete; properties of such concrete depend on the chemical composition, fineness, and burning temperature of SCBA. Approximately 1500 Million tons of sugarcane are annually produced over all the world which leave about 40-45 bagasse after juice crushing for sugar industry giving an average annual production of about 600 Million tons of bagasse as a waste material. This paper presents some findings on the effect of SCBA on workability, compressive strength and microstructure of interfacial zone of concrete and its performance is compared to some of the established CRMs namely Densified Silica Fume, Fly Ash and Microwave Incinerated Rice Husk Ash. Â© 2015 AIP Publishing LLC.